PSYCHOGENIC NONEPILEPTIC SEIZURES (PNES) VERSUS TRUE EPILEPSY: CLINICAL CHARACTERISTICS AND DIAGNOSTIC CHALLENGES. (CAHIERS MAGELLANES-NS, 2024)
Objective: This study aims to differentiate the clinical characteristics and diagnostic challenges of Psychogenic Nonepileptic Seizures (PNES) from true epilepsy in adult patients. An accurate diagnosis is critical to avoid unnecessary treatments and optimize patient management.Methods: A cross-sectional study was conducted on 80 adult patients presenting with seizure-like episodes at the Department of Neurology, Batra Hospital & Medical Research Centre, New Delhi. Detailed clinical evaluations, neuroimaging (MRI, CT), Electroencephalography (EEG), and Video EEG (VEEG) monitoring were performed. Patients were classified into PNES and true epilepsy groups, and statistical analyses were conducted to identify distinguishing features and diagnostic challenges.Results: Among the 80 patients, 35 were diagnosed with PNES, while 45 were diagnosed with true epilepsy. Key distinguishing features included the nature of seizure onset, duration, motor phenomena, and triggers. MRI and EEG findings showed significant differences between the two groups, with PNES patients often having normal neuroimaging and non-specific EEG changes. Diagnostic challenges were identified in overlapping clinical features, emphasizing the need for comprehensive diagnostic approaches.Conclusion: This study highlights the clinical differences and diagnostic challenges in distinguishing PNES from true epilepsy. A thorough evaluation incorporating clinical, neuroimaging, and VEEG data is essential to prevent misdiagnosis and ensure appropriate management.